User Readiness and Acceptance of Electronic Medical Record: A Partial Least Square Approach - Chairunnisah, Reni; Ismatullah, Nurul Khatimah; Andriani , Helmina (Procedia of Engineering and Life Science, 2024)
Electronic medical records (EMR) are increasingly popular in global healthcare to enhance service quality. However, transitioning to EMR poses challenges, particularly in adapting to the technology. Researchers are therefore interested in exploring the readiness and acceptance of EMR adoption using the Technology Readiness and Acceptance Model (TRAM). This study employs quantitative analytical methods and involves a sample size of 30 healthcare professionals responsible for medical record keeping. Total sampling was utilized to select participants. The variables examined in this research include Optimism (OPT), Innovativeness (INN), Discomfort (DIS), Insecurity (INS), Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Use Intention (USI). The study's findings, analyzed through Partial Least Squares (PLS), reveal that Innovativeness (INN) exerts the strongest influence on Perceived Ease of Use (PEOU) with a β-value of 0.434. Additionally, PEOU shows the most significant impact on Intention to Use (USI) with a β-value of 1.106. Approximately 71.8% of the variability in the USI variable is accounted for by Optimism (OPT), Innovativeness (INN), Discomfort (DIS), Insecurity (INS), Perceived Ease of Use (PEOU), and Perceived Usefulness (PU). At the same time, other factors outside the scope of this study explain the remaining variation. Keywords— Electronic Health Record, EMR, Readiness Index, Technology Readiness, Acceptance Model, TRAM